The biguanides metformin and phenformin inhibit angiogenesis, local and metastatic growth of breast cancer by targeting both neoplastic and microenvironment cells - Orecchioni, Stefania; Reggiani, Francesca; Talarico, Giovanna; Mancuso, Patrizia; Calleri, Angelica; Gregato, Giuliana; Labanca, Valentina; Noonan, Douglas M.; Dallaglio, Katiuscia; Albini, Adriana; Bertolini, Francesco (International journal of cancer, 2015)
The human white adipose tissue (WAT) contains progenitors with cooperative roles in breast cancer (BC) angiogenesis, local and metastatic progression. The biguanide Metformin (Met), commonly used for Type 2 diabetes, might have activity against BC and was found to inhibit angiogenesis in vivo. We studied Met and another biguanide, phenformin (Phe), in vitro and in vivo in BC models. In vitro, biguanides activated AMPK, inhibited Complex 1 of the respiratory chain and induced apoptosis of BC and WAT endothelial cells. In coculture, biguanides inhibited the production of several angiogenic proteins. In vivo, biguanides inhibited local and metastatic growth of triple negative and HER2+ BC in immune‐competent and immune‐deficient mice orthotopically injected with BC. Biguanides inhibited local and metastatic BC growth in a genetically engineered murine model model of HER2+ BC. In vivo, biguanides increased pimonidazole binding (but not HIF‐1 expression) of WAT progenitors, reduced tumor microvessel density and altered the vascular pericyte/endothelial cell ratio, so that cancer vessels displayed a dysplastic phenotype. Phe was significantly more active than Met both in vitro and in vivo. Considering their safety profile, biguanides deserve to be further investigated for BC prevention in high‐risk subjects, in combination with chemo and/or targeted therapy and/or as post‐therapy consolidation or maintenance therapy for the prevention of BC recurrence. What's new? Undifferentiated progenitor cells in white adipose tissue (WAT) have cooperative roles in breast cancer progression. In particular, they promote local tumor growth, angiogenesis, and metastasis—three processes shown in the present study to be inhibited by the biguanide drugs metformin and phenformin. Phenformin showed the highest levels of activity. The study is among the first to suggest that the two drugs exert their effects through direct activity against breast cancer cells, as well as through anti‐angiogenic activity against WAT progenitors. The conclusions were drawn from results obtained in vitro and in vivo in triple negative and HER2+ breast cancer models.